Situation Report: Bulgaria, 23 October 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Qualification Required for Collective Farm Managers Economic Delegation Returns from Moscow Georgi Traykov Vacations in the Soviet Union Conference on Party Ideological Work More Protests to Western Philosophers Bulgaria and Developments in Czechoslovakia